The influence of a first language: training nonnative listeners on voicing contrasts. Issue 6 (3rd July 2018) - Tuninetti, Alba; Tokowicz, Natasha
ABSTRACT: Learning how to perceive speech contrasts in a second language (L2) is influenced by many factors, including similarity to the first language (L1). Over five days, we trained native English and native Spanish speakers to perceive differences in the voiced Hindi contrast /p/-/p h / while recording their mismatch negativity (MMN) response before, during, and after training. Our results show that only native Spanish speakers showed a decrease in MMN amplitude following training, suggesting that the nonnative contrast was learned successfully, but this was not the case for native English speakers. This suggests that the acoustic and phonetic organisation of L1 differentially affects how we perceive and learn L2 sounds. We examine our results in the context of L2 learning and speech models, suggesting that further development on the difficulty of learning to perceive L2 speech should include more details on similarity to L1.